Genetic Characterization of Thyroglobulin and Leptin Genes in Pasundan Cattle at West Java - Widya Pintaka Bayu Putra; Saiful Anwar; Syahruddin Said; Romanos Albert Adhitya Indarto; Putri Wulandari (Buletin Peternakan, 2019)
The Thyroglobulin (TG) and Leptin (LEP) genes are two candidate genes that widely used for molecular selection to improve carcass traits in beef cattle. This research was carried out to identify the genetic characterization of TG and LEP genes from 47 heads of Pasundan cows at West Java using PCR-RFLP method. Research shows that TG gene of Pasundan cattle is monomorphic with C allele as the dominant allele (1.00). However, LEP gene of Pasundan cattle is polymorphic with C allele as the dominant allele (0.98) and T as the rare allele (0.02). The polymorphic informative content (PIC) and numberof effective allele (ne) values in the LEP gene in the animal studied were 0.04 and 1.04 respectively. It was concluded that TG/BstYI and LEP/Sau3AI gene in the present study can not be used as molecular selection in Pasundan cattle. These results are important as the basic information for preparing the molecular selection program in the future.